Eduardo Sánchez de Fuentes : un creador musical polémico - Pacheco Valera, Irina (Comparative Cultural Studies: European and Latin American Perspectives, 2020)
These pages, result of a bigger investigation about Eduardo Sánchez de Fuentes ‘s contributions to the musical patrimony of Cuba, attempts the rescue from a historical-social perspective, from the courses of the historical justice, because it is evidenced in this musician’s contributions in the field of the song, and its incursions in a meritorious way in the goods like: the operetta and in the opera, in the orchestra and in the ballet, in the oratory and in the symphonic poem, in the critic and in the musicology. This article refers to some of the fundamental budgets approached in the work of Sánchez de Fuentes, with the purpose of investigating its polemic universe in itself and by the light of the cultural counterpoint of its time, and this way to surrender deserts homage to this famous musicologist.